Mary McLeod in conversation with Salomon Frausto and Leá-Catherine Szacka - Mary McLeod (Footprint)
In February 1989, architectural historian and theorist Mary McLeod published her now seminal essay entitled ‘Architecture and Politics in the Reagan Era: From Postmodernism to Deconstructivism’ in Assemblage 8. In the essay, she examined the relationship between architecture and politics in the 1980s, a time of unprecedented change. The following conversation discusses the circumstances under which the essay was originally written and offers her reflections thirty years later to think about the relationship between architecture and populism today.